Effects of Linguistic Distance on Second Language Brain Activations in Bilinguals: An Exploratory Coordinate-Based Meta-Analysis - Cargnelutti, Elisa; Tomasino, Barbara; Fabbro, Franco (Frontiers in Human Neuroscience, 2022)
In this quantitative meta-analysis, we used the activation likelihood estimation approach to address the effects of linguistic distance between first (L1) and second (L2) languages on language-related brain activations. In particular, we investigated how L2-related networks may change in response to linguistic distance from L1. Thus, we examined L2 brain activations in two groups of participants with English as L2 and either (a) a European language (European group, n = 13 studies) or (b) Chinese (Chinese group, n = 18 studies) as L1. We further explored the modulatory effect of age of appropriation and proficiency of L2. We found that, irrespective of L1-L2 distance – and to extent – irrespective of L2 proficiency, L2 recruits brain areas supporting higher-order cognitive functions (e.g., cognitive control), although with group-specific differences (e.g., the insula region in the European group and the frontal cortex in the Chinese group). The Chinese group also selectively activated the parietal lobe, but this did not occur in the proficient subgroup with high L2 proficiency. These preliminary results highlight the relevance of linguistic distance and call for future research to generalize findings to other language pairs and shed further light on the interaction between linguistic distance and age of appropriation and proficiency of L2.